Internalization of Students' Ecological Intelligence Through Contextual Teaching and Learning In Akidah Akhlak Subjects at Madrasah Tsanawiyah - Welly Kuswanto; Asep Rahmatullah; Abdul Chamid; Ahmad Nur Kholiq (Global Education Journal, 2025)
The irregularity of seasons and the impact of climate change in Indonesia demand a transformation in religious education that is not only based on theoretical knowledge but also responsive to environmental crises. This study aims to deeply analyze the mechanism of internalizing ecological values in the Akidah Akhlak subject through the Contextual Teaching and Learning (CTL) strategy at MTs Anwarus Salaf. Using a descriptive-analytical qualitative approach, this study involved an Akidah Akhlak teacher and 210 students as research subjects. Data were collected through participant observation, in-depth interviews, and documentation studies, which were then analyzed using the Miles, Huberman, and Saldaña model with the assistance of Atlas.ti software. The results show that the internalization of ecological intelligence occurs through a systematic CTL cycle, where constructivism and inquiry components successfully shift the student paradigm from textual understanding to contextual awareness of the fasad (earthly destruction) phenomenon. Teacher exemplary behavior through modeling (uswatun hasanah) and measured habituation through the Moral Control Book (Buku Kendali Akhlak) proved effective in transforming student motivation from extrinsic to intrinsic-transcendental. The main finding of this study constructs the Khalifah fi al-Ardh paradigm as a new identity for students, which gives birth to eco-spirituality where nature conservation is understood as a manifestation of tawhid and moral accountability before Allah SWT. This study recommends a reorientation of integrative religious education curricula to form a generation that is intellectually brilliant and has ethical responsibility for the sustainability of the universe.